Radiofrequency Ablation as an Alternative and Novel Procedure in the Intraepithelial Neoplasia Management: A Systematic Scoping Review - Hamid Reihani; Sepehr Ebrahimi‐Dehkordi; Reza Moshfeghinia; Amirhossein Ghiasi‐Nejad; Kiarash Noorizadeh; Reza Heidari‐Soureshjani (Health Science Reports)
ABSTRACT Background and Aims Radiofrequency ablation (RFA) has emerged as a promising minimally invasive technique for eliminating intraepithelial neoplasia (IEN). We reviewed current evidence investigating the role of RFA in managing different types of IEN. Methods A systematic review was conducted to assess the current evidence for the use of RFA in managing various types of IEN. A three‐step search strategy was employed, involving keyword extraction, comprehensive database searching (PubMed, Scopus, Web of Science, Embase, and Google Scholar), and reference screening. Results Thirty‐two articles were included in this review, and most of the literature reported the features of RFA in the esophagus‐related IENs (68.7%). RFA treatment was also found to effectively address gastric (9.3%), anal (12.5%), and cervical (9.3%) IENs. The general opinion on using RFA in Barrett's esophagus (BE) was its combination therapy with the endoscopic mucosal resection (EMR) methods, which suggested better outcomes than RFA/EMR monotherapy. RFA was not preferred treatment for high‐grade gastric dysplasia, but it was effective for the low‐grade type. Conclusion As a minimally invasive, safe, and effective procedure, RFA holds promise for addressing lesions associated with BE, gastric, anal, and cervical IEN; However, the scope and gaps related to RFA therapy require to be explored precisely.